ANALISIS PROFITABILITAS DALAM MEMEDIASI PENGARUH SOLVABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN USAHA PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2021 - Andriza Bintang Pramudya; Wisnu Mawardi (Diponegoro Journal of Management, 2023)
ABSTRACT The purpose study is to analyze the magnitude effect of the mediating role called profitability on the effect of solvency and firm size on firm value. There is one dependent variable, firm value, while there are two pure independent variables: solvency and firm size, and one mediating variable, it is profitability.The number of samples in this study, a sum of all 196 samples of property and real estate companies listed on the Indonesia Stock Exchange (IDX), is determined using the census sampling method. This study uses secondary data sourced from IDX Statistics 2017, 2018, 2019, 2020 and 2021 on companies in that sector. There is also an analytical method used in this study is a multiple linear regression analysis in which the classical assumption is tested first, which includes the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test.The results expose that solvency (DER) has no significant negative effect on profitability (ROA). Firm size (Ln Assets) has a significant positive effect on profitability (ROA). Solvency (DER) has a significant positive effect on firm value (PBV). Firm size (Ln Assets) has a significant negative effect on firm value (PBV). Profitability (ROA) has no significant negative effect on firm value (PBV). Profitability (ROA) does not mediate the effect of solvency (DER) on firm value (PBV). Profitability (ROA) does not mediate the effect of firm size (Ln Assets) on firm value (PBV)